Energy Ratio (E-R) for the Standard Penetration Test Based on Measured Field Tests - Lukiantchuki, J. A.; Bernardes, G. P. [UNESP]; Esquivel, E. R. (Brazilian Soc Soil Mechanics & Geotechnical Engineering, 2017)
The Standard Penetration Test (SPT) is often used to estimate the soil parameters for geotechnical design projects, using the N SPT index. However, these estimates are performed based on empirical correlations without any scientific basis. Moreover, the test has a large inherent results dispersion due to the use of different types of equipment and execution procedures. Since the N SPT index depends on the amount of energy that is effectively transmitted to the sampler during the hammer fall, it is fundamental to be able to estimate this energy. Given the importance of estimating the energy that reaches the SPT sampler, an instrumented subassembly was developed in order to simultaneously assess the amount of energy transmitted to the drill rods, at sections just above the sampler and just below the anvil. This paper presents a series of SPT experimental results carried out in two different sites located in the State of Sao Paulo, using two different equipment set-ups (with manual and automatic tripping mechanisms), enabling the assessment of the top and bottom energy ratio under different conditions. Results show that for hand lifting hammer and automatic trip hammer systems the difference in the energy ratio is not significant. However, the dispersion of the results for the hand lifting hammer system is more pronounced due to execution procedures, equipment and operators.
Keywords: penetration test; SPT test; energy; energy ratio; dynamic instrumentation; foundations